Cognitive Avoidance Questionnaire: Factor structure and psychometric properties. - Latorre Postigo, José Miguel; Nieto López, Marta; Font Payeras, María Antonia; Ros Segura, Laura; Heras, Jesús; Ricarte Trives, Jorge Javier (Anales de Psicología / Annals of Psychology, 2020)
Cognitive avoidance refers to strategies and efforts toward prevention of aversive experiences and events that provoke anxiety. The present study analyzed the factor structure and psychometric properties of the Spanish version of the Cognitive Avoidance Questionnaire (CAQ; Sexton & Dugas, 2008), an instrument that assesses five worry-related cognitive avoidance strategies. The Spanish translation was administered to a non-clinical sample of 614 participants (18-82 years). The total scale and subscales showed good to excellent internal consistency. Using confirmatory factor analysis, a five-factor model showed a good fit between the theoretical structure and the empirical data. Evidence of convergent and discriminant validity was obtained through analysis of the correlations of the questionnaire with measures of worry, thought suppression, rumination and coping styles. The results yielded satisfactory preliminary data on the Spanish adaptation of the CAQ, which could provide for further advances in clinical practice and research on cognitive processes and anxiety disorders.